Faktor-Faktor Tempat Tinggal Bagi Masyarakat Berpenghasilan Rendah Di Kelurahan Pudak Payung - Aditya Zulfikar Firdaus; Mardwi Rahdriawan (Teknik PWK (Perencanaan Wilayah Kota), 2021)
Housing and settlements are problems that develop in line with population growth increasing residential needs. Along with the increasing demand for land for residential development, there is also land value development.  Besides, these problems also result in a reduced empty area that can be used for housing and makes land prices more expensive. So, a low-income community's limitations in obtaining livable houses causing them to have gotten houses independently. Self-help houses built by a low-income community are identical to uninhabitable homes because they ignore aspects of livable standards. This study aims to determine the factors that affect a low-income neighbourhood in residence regarding a low-income neighbourhood's characteristics. The method used is quantitative and uses descriptive analysis techniques and crosstabs analysis. The results of this study indicate that what affects the low-income community living in the Pudak Payung Village are environmental comfort factors with a value of 91%, accessibility with an amount of 55%, waste with a value of 93%, electricity with an amount of 54% and clean water with an amount of  100%. While the analysis that has a relationship based on the chi-square test is the accessibility with 0.049, electricity with education is 0.01, and heat with income is 0.00.